Anisole is an environmentally friendly fumigant for postharvest pest control. (September 2021) - Yang, Xiangbing; Liu, Yong-Biao
Abstract: Plant essential oils have demonstrated insecticidal effects but not many are as effective as currently used fumigants. We evaluated anisole, a volatile compound extracted from aniseed, for control of four insect pests including adult rice weevil, Sitophilus oryzae (L.) (Coleoptera: Curculionidae), granary weevil, Sitophilus granarius (L.) (Coleoptera: Curculionidae), and confused flour beetle, Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae), and a fresh produce product pest, western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), in the laboratory tests. Anisole fumigations were effective against all four pests. At a dose of 100 μL/L, anisole fumigation completely controlled S. granarius and S. oryzae in 24 and 16 h, respectively. At a dose of 150 μL/L, complete control of the two weevils was achieved in 16 and 8 h, respectively. T. confusum was completely controlled in 16 and 8 h with anisole fumigations at 400 μL/L and 600 μL/L respectively. F. occidentalis was 100% controlled in 8 and 6 h treatments with anisole at doses of 150 μL/L and 300 μL/L, respectively. The median lethal times (LT50 ) of anisole fumigation at 50 μL/L were 0.6 and 0.5 h for S. granarius and S. oryzae, respectively. LT50 for T. confusum at 600 μL/L was 2.9 h. In a 16 h confirmatory test in a mini silo, anisole fumigation achieved 100% control of rice weevil at different depth of stored corn. This study demonstrated that anisole fumigation was effective against insects. Therefore, anisole fumigation has potential as an environmentally friendly, alternative fumigant for postharvest pest control. Highlights: Anisole was evaluated as a potential fumigant against four insects in laboratory tests. Effective control of all four insects: rice weevil, granary weevil, confused flour beetle, and western flower thrips was achieved. Anisole fumigation also controlled rice weevil adults at different depths in stored corn in a mini silo. Anisole has potential to be an environmentally friendly fumigant for postharvest pest control.